Application Potential of Cyanide Hydratase from Exidia glandulosa: Free Cyanide Removal from Simulated Industrial Effluents - Anastasia Sedova (MDPI AG, 2021)
Industries such as mining, cokemaking, (petro)chemical and electroplating produce effluents that contain free cyanide (fCN = HCN + CN−). Currently, fCN is mainly removed by (physico)chemical methods or by biotreatment with activated sludge. Cyanide hydratases (CynHs) (EC 4.2.1.66), which convert fCN to the much less toxic formamide, have been considered for a mild approach to wastewater decyanation. However, few data are available to evaluate the application potential of CynHs. In this study, we used a new CynH from Exidia glandulosa (protein KZV92691.1 designated NitEg by us), which was overproduced in Escherichia coli. The purified NitEg was highly active for fCN with 784 U/mg protein, kcat 927/s and kcat/KM 42/s/mM. It exhibited optimal activities at pH approximately 6–9 and 40–45 °C. It was quite stable in this pH range, and retained approximately 40% activity at 37 °C after 1 day. Silver and copper ions (1 mM) decreased its activity by 30–40%. The removal of 98–100% fCN was achieved for 0.6–100 mM fCN. Moreover, thiocyanate, sulfide, ammonia or phenol added in amounts typical of industrial effluents did not significantly reduce the fCN conversion, while electroplating effluents may need to be diluted due to high fCN and metal content. The ease of preparation of NitEg, its high specific activity, robustness and long shelf life make it a promising biocatalyst for the detoxification of fCN.